2009
DOI: 10.1243/09544089jpme253
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion model for thin layer drying process of corn

Abstract: In this study, single-layer drying behaviour of corn is simulated by liquid diffusion model by using the experimental data for drying temperatures between 40 and 70 °C and for a drying rate of 2 m/s. Three different geometries representing a corn grain, slab, sphere, and cylinder are taken into consideration to specify the geometry which yields best results. The drying curves are obtained by minimizing the sum of squared differences between experimental data and theoretical predictions. Results show that dryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Among the tested models, the diffusion approach model was the most suitable for expressing the moisture ratio at different temperatures with almost the lowest MSE and highest R-square. The diffusion approach was also used for describing the drying process of pomelo (Yildiz & İzli, 2019) and corn (Hacihafizoğlu et al, 2009). Another study on tarragon also showed that the diffusion approach model gave the best fit to predict drying behavior (Arabhosseini et al, 2009).…”
Section: Applying Mathematical Modelmentioning
confidence: 99%
“…Among the tested models, the diffusion approach model was the most suitable for expressing the moisture ratio at different temperatures with almost the lowest MSE and highest R-square. The diffusion approach was also used for describing the drying process of pomelo (Yildiz & İzli, 2019) and corn (Hacihafizoğlu et al, 2009). Another study on tarragon also showed that the diffusion approach model gave the best fit to predict drying behavior (Arabhosseini et al, 2009).…”
Section: Applying Mathematical Modelmentioning
confidence: 99%
“…The moisture content of foodstuff should be reduced in order to prevent deterioration during storage after harvesting. The moisture content of the corn after harvesting is around 24-25% (dry basis) and must be reduced below 14% (dry basis) by a suitable drying process [1].…”
Section: Introductionmentioning
confidence: 99%
“…Doymaz and Pala [5] used empirical exponential model and Page model for describing the thin layer drying process of corn and found that the Page model is better than the exponential model. Hacihafizoglu et al [1] used a liquid diffusion model for the simulation of continuous drying of corn with an initial mois-THERMAL SCIENCE: Year 2019, Vol. 23,No.…”
Section: Introductionmentioning
confidence: 99%
“…11 In many theoretical studies on convective drying modeling, the temperature of the material during the drying process was assumed to be constant at drying air temperature and the effect of the drying air temperature was considered in the diffusion coefficient. [12][13][14][15][16][17][18][19] This assumption results in a higher drying rate due to the higher diffusion coefficient.…”
mentioning
confidence: 99%
“…The first is a Dirichlet-type boundary condition and the material surface is assumed to be at equilibrium moisture content. This assumption, which has been used in many drying models, [12][13][14][15][16][17][18][19] causes higher mass transfer rates at the material surface. The second type of boundary condition, which is more realistic, is a Neumann-type boundary condition, and it has also been used in several studies.…”
mentioning
confidence: 99%